Selective bromodomain and extra-terminal bromodomain inhibitor inactivates macrophages and hepatic stellate cells to inhibit liver inflammation and fibrosis. Issue 4 (1st April 2022) - Fu, Rong; Zu, Shi-Jia; Liu, Yan-Jun; Li, Jia-Cheng; Dang, Wen-Zhen; Liao, Li-Ping; Liu, Li-Ping; Chen, Pan-Yu; Huang, He-Ming; Wu, Kang-Hui; Zhou, Bing; Pan, Qin; et al.
ABSTRACT: Liver fibrosis occurs following inflammation triggered by the integrated actions of activated liver-resident macrophages (Kupffer cells) and hepatic stellate cells (HSCs), and the multiplicity of these mechanisms complicates drug therapy. Here, we demonstrate that the selective bromodomain and extra-terminal (BET) bromodomain inhibitor compound38 can block both the Janus kinase-signal transducer and activator of transcription and mitogen-activated protein kinase signaling pathways in macrophages, which decreased their secretion of proinflammatory cytokines in a dose-dependent manner. The inactivation of macrophages attenuated lipopolysaccharide-induced injurious inflammation concurrent with a reduction in F4/80+ cells, proinflammatory cytokine levels, and neutrophil infiltration. Moreover, compound 38 inhibited the Wnt/β-catenin and transforming growth factor-beta/SMAD signaling pathways to abolish the activation of HSCs. In vivo, compound 38 significantly decreased the collagen deposition and fibrotic area of a CCl4 -induced liver fibrosis model, and restored the deficiency of activated HSCs and the upregulation of liver inflammation. These results highlight the potential role of compound 38 in treating liver fibrosis considering its simultaneous inhibitory effects on liver inflammation and related fibrosis. Graphical abstract: uf0001